Different Subgroups of Cholinergic Neurons in the Basal Forebrain Are Distinctly Innervated by the Olfactory Regions and Activated Differentially in Olfactory Memory Retrieval - Zheng, Yingwei; Feng, Shouya; Zhu, Xutao; Jiang, Wentao; Wen, Pengjie; Ye, Feiyang; Rao, Xiaoping; Jin, Sen; He, Xiaobin; Xu, Fuqiang (Frontiers in Neural Circuits, 2018)
The mammalian basal forebrain (BF), a heterogenous structure providing the primary cholinergic inputs to cortical and limbic structures, plays a crucial role in various physiological processes such as learning/memory and attention. Despite the involvement of the BF cholinergic neurons (BFCNs) in olfaction related memory has been reported, the underlying neural circuits remain poorly understood. Here, we combined viral trans-synaptic tracing systems and ChAT-cre transgenic mice to systematically reveal the relationship between the olfactory system and the different subsets of BFCNs. The retrograde adeno-associated virus and rabies virus (AAV-RV) tracing showed that different subregional BFCNs received diverse inputs from multiple olfactory cortices. The cholinergic neurons in medial and caudal horizontal diagonal band Broca (HDB), magnocellular preoptic area (MCPO) and ventral substantia innominate (SI; hereafter HMS complex, HMSc) received the inputs from the entire olfactory system such as the olfactory bulb (OB), anterior olfactory nucleus (AON), entorhinal cortex (ENT), basolateral amygdala and especially the piriform cortex (PC) and hippocampus (HIP); while medial septum (MS/DB) and a part of rostral HDB (hereafter MS/DB complex, MS/DBc), predominantly from HIP; and nucleus basalis Meynert (NBM) and dorsal SI (hereafter NBM complex, NBMc), mainly from the central amygdala. The anterograde vesicular stomatitis virus (VSV) tracing further validated that the major target of the OB to the BF is HMSc. To correlate these structural relations between the BFCNs and olfactory functions, the neurons activated in the BF during olfaction related task were mapped with c-fos immunostaining. It was found that some of the BFCNs were activated in go/no-go olfactory discrimination task, but with different activated patterns. Interestingly, the BFCNs in HMSc were more significantly activated than the other subregions. Therefore, our data have demonstrated that among the different subgroups of BFCNs, HMSc is more closely related to the olfactory system, both structurally and functionally. This work provides the evidence for distinct roles of different subsets of BFNCs in olfaction associated memory.